Green production of fluorescent carbon quantum dots based on pine wood and its application in the detection of Fe3+. (1st August 2020) - Zhao, Siyu; Song, Xueping; Chai, Xinyu; Zhao, Peitao; He, Hui; Liu, Zhenwei
Abstract: Carbon quantum dots (CQDs) have novel applications as fluorescent nanomaterials in various fields. In this study, a green hydrothermal carbonisation (HTC) method is proposed to produce CQDs from pine wood (P-CQDs). The P-CQDs exhibited excellent fluorescence characteristics, with the optimal excitation wavelength being 330 nm and a corresponding emission wavelength of 447 nm. A blue light emission under ultraviolet light was observed and a typical graphene structure was seen in the HR-TEM images with a fringe spacing of 0.21 nm. Moreover, the mechanism of P-CQD formation during the HTC process was proposed. It was observed that P-CQDs demonstrated an aromatic polymer structure rich in oxygen-containing groups. This is because of the condensation, chain breaking, and chain forming reactions occurring among the hydrolytic products of the cellulose, hemicellulose, and lignin in pine wood. The fluorescence quenching results indicated that the P-CQDs selectively detected Fe 3+ in an aqueous phase. This implies that these CQDs have broad application prospects for Fe 3+ detection. More importantly, this signifies that the large-scale and low-cost production of CQDs and Fe 3+ sensors will now be possible. Graphical abstract: Image 1 Highlights: One-pot hydrothermal treatment of pine wood was used to prepare P-CQDs. P-CQDs have aromatic structure and are rich in oxygen-containing groups. Reactions among hydrolysates of major components of pine led to the formation of CQDs. Fe 3+ could be selectively identified by P-CQDs and its detection limit was 355.4 nmol.